Evaluation of Land Capability for Forest Trees Species and Multi Purpose Trees Species in Tuntungan Sub-distric, Medan City - Elvira Sihotang; Rahmawaty Rahmawaty; Abdul Rauf (Program studi Kehutanan USU, 2016)
Currently, there is a tendency to use the land for the benefit of the economy , which could increase income. Where, land use based-on market price, led to alternation of type of crops grown. Planning of the use of land should focus on balance and environmental sustainability. The purpose study was to evaluate the ability of a class of land for forest plants and multi trees species in the district multipurpose in Medan Tuntungan sub-distric. Matching method and Geographic Information Systems was used to evaluate the study. There were 9 unit of lands which the land capability classification was dominated by class I with a limiting factor to the erosion hazard, suggesting that it was necessary to the improvement of land that paralled to contour planting, terracing, and planting land cover . Land units VII and IX was the most land units inappropriate. This land units should be established as a natural protected area because the slopes are difficult to manage . Keywords: GI, Land capability, Medan Tuntungan Sub-distric